2011
DOI: 10.1124/dmd.111.042283
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Glucuronidation of the Antibacterial Triclocarban and Its Oxidative Metabolites

Abstract: ABSTRACT:Triclocarban (3,4,4-trichlorocarbanilide; TCC) is widely used as an antibacterial in bar soaps. During use of these soaps, a significant portion of TCC is absorbed by humans. For the elimination from the body, glucuronidation plays a key role in both biliary and renal clearance. To investigate this metabolic pathway, we performed microsomal incubations of TCC and its hydroxylated metabolites 2-OH-TCC, 3-OH-TCC, and 6-OH-TCC. Using a new liquid chromatography-UV-mass spectrometry method, we could show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
(57 reference statements)
0
27
0
Order By: Relevance
“…TPPU shows good metabolic stability when incubated with primary rat hepatocytes. It is interesting that apparently no direct phase II conjugation by liver glucuronosyltransferases takes place, though the direct N -glucuronidation has been described for the structurally similar triclocarban 38 . Moreover, TPPU seems to be stable by phase I metabolism since 90% of TPPU was remained in the medium of primary rat hepatocytes after 20 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…TPPU shows good metabolic stability when incubated with primary rat hepatocytes. It is interesting that apparently no direct phase II conjugation by liver glucuronosyltransferases takes place, though the direct N -glucuronidation has been described for the structurally similar triclocarban 38 . Moreover, TPPU seems to be stable by phase I metabolism since 90% of TPPU was remained in the medium of primary rat hepatocytes after 20 h of incubation.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to extrapolate from the observed formation rate in vitro to the generation of metabolites in tissues in vivo. TCC conversion to both oxidative metabolites and N-glucuronides is substantially underpredicted by in vitro microsomal incubations (Baumann et al, 2010;Schebb et al, 2012b). This low predictability is likely related to the poor water solubility of the compound, 142 nM (Snyder et al, 2010), causing a low effective concentration in the assays.…”
Section: ) These Are Likely the [M-h]mentioning
confidence: 99%
“…Showering with antibacterial soap results in the absorption of ;0.6% of the applied amount of TCC (Schebb et al, 2011b). Several studies have shown that TCC is extensively metabolized in fish, rodents, monkeys, and humans, leading to several phase I and phase II metabolites (Baumann et al, 2010;Schebb et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations